2021
DOI: 10.1097/bpb.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cone beam computed tomography, standard computed tomography and plain radiographs in the evaluation of medial epicondyle humerus fractures

Abstract: The ideal technique to measure medial epicondyle humerus fracture displacement minimizes radiation exposure while maximizing measurement accuracy and reliability. This study compares the radiation exposure and accuracy of displacement measurements of the four-view X-ray examination (XR), computed tomography (CT) and in-clinic cone-beam CT (CBCT). A cadaveric humerus underwent medial epicondyle osteotomy. The fragment was fixed to the humerus at clinically relevant displacements (6 to 18 mm). Dosimeters were pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The effect of CT techniques on the reliability of classification systems has been extensively studied and their additional value can still be questioned [ 10 12 ]. For tibial plateau fractures, Millar et al [ 13 ] provided a comprehensive analysis of the reliability of classification systems based on studies published until October 2016, and showed that five classification systems were tested for inter- and intra-observer reliability: AO/OTA [ 5 ], Schatzker et al [ 4 ], Duparc and Ficat [ 6 ], Hohl[ 3 ], and Luo et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of CT techniques on the reliability of classification systems has been extensively studied and their additional value can still be questioned [ 10 12 ]. For tibial plateau fractures, Millar et al [ 13 ] provided a comprehensive analysis of the reliability of classification systems based on studies published until October 2016, and showed that five classification systems were tested for inter- and intra-observer reliability: AO/OTA [ 5 ], Schatzker et al [ 4 ], Duparc and Ficat [ 6 ], Hohl[ 3 ], and Luo et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%